Mechanisms of MTA3 in cancer and related diseases and its clinical applications - Tang, Yan; Li, Xiao-Jiao; Ao, Hui; Liu, Qian-Guo; Zheng, Xiao-Fu; Liao, Chang-Li; Li, Jun; Wu, Yong-Kang (Frontiers in Oncology, 2026)
Metastasis-associated protein 3 (MTA3), a key member of the MTA family, is an integral component of the nucleosome remodeling and deacetylase complex, with widespread expression across diverse human tissues and organs. By modulating epigenetic modifications, MTA3 is instrumental in regulating vital physiological processes, including cell differentiation, apoptosis, and metabolism. It plays a crucial role in maintaining normal tissue homeostasis and exerts a significant regulatory influence on pathological conditions, notably cancer and other diseases. This review presents a comprehensive evaluation of the molecular structural characteristics and biological functions of MTA3, providing a detailed overview of its mechanistic role in tumorigenesis and disease progression. Its unique tissue-specific expression patterns and dual functional roles as an oncogene or tumor suppressor, depending on the cellular and disease context, are highlighted. Moreover, by integrating recent research advancements, the feasibility and potential clinical translational value of using MTA3 as a diagnostic and prognostic biomarker, as well as a therapeutic target in developing novel disease intervention strategies, are evaluated in this review. This study aimed to establish a robust theoretical foundation and provide novel research perspectives to support future endeavors focused on improving patient outcomes by precisely modulating MTA3 activity.